Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To determine the [tex]$x$[/tex]-intercept of the function [tex]\( y = \frac{6x - 18}{x + 9} \)[/tex], we need to find the value of [tex]\( x \)[/tex] where [tex]\( y \)[/tex] is equal to zero. In other words, we need to solve the equation [tex]\( y = 0 \)[/tex].
Here's the step-by-step process:
1. Set [tex]\( y \)[/tex] equal to zero:
[tex]\[ 0 = \frac{6x - 18}{x + 9} \][/tex]
2. To eliminate the denominator, multiply both sides of the equation by [tex]\((x + 9)\)[/tex]:
[tex]\[ 0 \cdot (x + 9) = 6x - 18 \][/tex]
Since anything multiplied by zero is zero, this simplifies to:
[tex]\[ 0 = 6x - 18 \][/tex]
3. Now, solve for [tex]\( x \)[/tex] by isolating [tex]\( x \)[/tex]:
[tex]\[ 6x - 18 = 0 \][/tex]
4. Add 18 to both sides of the equation to move the constant term to the right side:
[tex]\[ 6x = 18 \][/tex]
5. Lastly, divide both sides by 6 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{18}{6} \][/tex]
[tex]\[ x = 3 \][/tex]
Therefore, the [tex]$x$[/tex]-intercept of the function [tex]\( y = \frac{6x - 18}{x + 9} \)[/tex] is [tex]\((3, 0)\)[/tex].
Here's the step-by-step process:
1. Set [tex]\( y \)[/tex] equal to zero:
[tex]\[ 0 = \frac{6x - 18}{x + 9} \][/tex]
2. To eliminate the denominator, multiply both sides of the equation by [tex]\((x + 9)\)[/tex]:
[tex]\[ 0 \cdot (x + 9) = 6x - 18 \][/tex]
Since anything multiplied by zero is zero, this simplifies to:
[tex]\[ 0 = 6x - 18 \][/tex]
3. Now, solve for [tex]\( x \)[/tex] by isolating [tex]\( x \)[/tex]:
[tex]\[ 6x - 18 = 0 \][/tex]
4. Add 18 to both sides of the equation to move the constant term to the right side:
[tex]\[ 6x = 18 \][/tex]
5. Lastly, divide both sides by 6 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{18}{6} \][/tex]
[tex]\[ x = 3 \][/tex]
Therefore, the [tex]$x$[/tex]-intercept of the function [tex]\( y = \frac{6x - 18}{x + 9} \)[/tex] is [tex]\((3, 0)\)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.